Body size and body composition change trends in preschool children over a period of five years - Horvat, Vatroslav, kineziolog (Array, 2009)
Abstract: The study investigated the changes of body size and composition in the sample of 296 preschool urban dwelling children aged 6.5 ± 0.8 years over a period of five years. Fourteen anthropometric measures were taken. Body mass index (BMI), the sum of skinfolds, the fat percentage and fat-free mass (FFM) were computed. The significant changes in body size and composition over the observed period were found. A significant increase in height and weight was registered in the boys. The average BMI did not change significantly while body fatness was significantly enlarged (from 10.79% to 16.96%, P=0.0001) with no changes in FFM. In the girls there were no significant changes in height, weight and BMI, while again fatness was significantly enlarged (from 15.5% to even 19.44%, P=0.003), with a significantly decreased share of FFM (P<0.05), primarily due to the decrease of the upper limbs’ muscular mass. The greatest contribution to the discriminant function was obtained by the skinfolds in the boys and by the arm length and forearm circumference in the girls